Diffuse Tongue Enlargement Related to Amyloidosis: A Case Report - Abdulaziz Alwakeel; Mohamed Rahoof Arakkalvettath; Samia Nawaz; Faris Albalawi; Abdullatif Alatawi (Journal of Pharmacy and Bioallied Sciences, 2025)
Amyloidosis is typically classified as either a systemic or localized condition. In the head and neck region can present as either localized or systemic. The tongue and larynx are the most commonly affected areas, with the tongue being the most frequent site of systemic involvement. The aim for reporting this case is shows the case of amyloidosis present in the tongue and shows diffuse tongue enlargement. 82 years old, male refer to oral medicine clinic because he complain for difficulty during eating, swelling and heaviness in his tongue clinical examination shows diffuse tongue enlargement with multiple yellow nodule in the lateral border area of tongue. Clinical differential diagnosis for our case macroglossia related to amyloidosis, hypothyroidism, multiple mucosal neuroma related to neurofibromatosis. Biopsy was taken from anterior lateral side of tongue and it has been send to histopathological evaluation, the histopathology result shows amorphous eosinophilic material deposit in sub mucosal area suggested amyloid like appearance, Congo red done for more evaluation and shows positivity for amyloid material. So, finally our diagnosis for presented case was oral amyloidosis, patient treated by topical corticosteroid (prednisolone 5mg time a day as mouth wash) but shows little improvement, patient after that has been referred to internal medicine department to confirm the type of amyloidosis and treat by proper medication. The amyloidosis can be presented local or systemic, so the tongue one of the organs that can be affected by disease, careful clinical examination for patient has diffuse tongue enlargement and biopsy taken is mandatory to get proper diagnosis and treatment is pure native aortic regurgitation are however still under research.